The motives, academic performance, and career prospects of Gazan medical students abroad: a cross-sectional study. (July 2021) - Alser, Muath; Alkhatib, Mo'min; Alnakhala, Ahmed; Barhoom, Mohammed Ibrahim
Abstract: Background: In Gaza, 2 million people have been affected by more than 13 years of strict land, air, and sea blockades and three wars, during which over 4000 people have been killed and many more have been injured. Additional severe effects have been seen on lives, aspirations, and prospects. Given the conditions, medical students have many competing reasons for and against studying medicine abroad. We investigated motives, academic situations, and future plans of the upcoming generation of doctors in Gaza, occupied Palestinian territory. Methods: We did a questionnaire-based cross-sectional study involving Palestinian medical students originally from Gaza who were studying at the largest five medical schools in Egypt (Cairo, Ain Shams, Alexandria, Mansoura, and Zagazig Universities). We used a self-designed questionnaire developed from previous similar studies and created on Google Forms (Google, Menlo Park, CA, USA). A pilot study of 37 participants was done to test the comprehensibility of questions and the time needed to complete the questionnaire. After being updated, the questionnaire was distributed in August and September, 2018, to individuals who provided verbal informed decision to participate. Analysis of the results was performed with SPSS version 22. Findings: Of 453 questionnaires given to students, 340 (75%) were returned completed. The mean age of respondents was 21·7 (SD 1·8) years; 225 (66%) were men and 115 (34%) were women. Excellence was achieved in secondary school examinations (result ≥90%) by 315 (93%) of students, but only 26 (8%) of students achieved excellence in their first year of medical school (examination results ≥85%). 317 students (93%) reported that they chose their medical schools independently without pressure from their families. Among the 115 women, 70 (61%) went to a third party to persuade their parents to allow them to study abroad. Of ten motives to study medicine given in the questionnaire, "to relieve pains" and "childhood dream" were the most frequently selected among the 340 respondents, chosen by 228 (67%) and 208 (61%), respectively. 104 (31%) reported they were seeking freedom more than to study medicine. 214 (63%) of students had at least one relative who had been physically injured in or killed during of one of the wars in Gaza. Most students (n=278 [82%]) were delayed from starting at their medical school due to border closures and 189 (56%) had been unable to attend for at least one semester. Since starting at medical school, 269 (79%) of 340 respondents had visited Gaza only once or not at all. 55 (16%) intended never return to Gaza and 209 (62%) reported that they wanted to specialise and work abroad for a period and then return to Gaza. Of the remainder, 64 (19%) wanted to specialise abroad then return to work in Gaza, and 12 (3%) wanted to specialise and work in Gaza. Interpretation: The motives, academic performance, and career prospects of Gazan medical students studying in Egypt are influenced in many ways by the situation in Gaza, some of which could worsen the already bad condition of medical care in Gaza. Awareness and supportive programmes for Gazan medical students should be encouraged to improve the quality of health care providers in Gaza. Funding: None.